A string-based cohesive zone model for interlaminar delamination. (July 2017) - Zhang, Liang; Gao, Zhenyuan; Yu, Wenbin
Highlights: A string-based cohesive zone model (CZM) for interlaminar delamination is developed. Its cohesive elements behave reliably when deformed along complex separation paths. They can display realistic critical energy release rate-mode mixture ratio relations. The interface parameters are calibrated from experimental data. The present CZM is validated through simulating flexural tests using Abaqus/Explicit. The interfacial strength is found to affect the predicted load–displacement curves. Abstract: The objective of this paper is to develop a string-based cohesive zone model (CZM) for interlaminar delamination, whose associated cohesive elements behave reliably and consistently when deformed along complex separation paths and can display experimental critical energy release rate–mode mixture ratio relationships. Each cohesive element is idealized as a deformable string exhibiting path dependent damage behavior, and the thermodynamic equations are formulated in a generalized standard manner. A damage model having a path dependence function is developed. The rate form of the cohesive law is subsequently derived. The path dependence function is constructed such that each cohesive element can exhibit designated, possibly sophisticated mixed-mode behavior. The interface parameters associated with the present CZM are calibrated from experimental data. The present CZM is validated through simulating a series of flexural tests using Abaqus/Explicit. It is found to be capable of producing reliable simulation results. The interfacial strength is found to affect the predicted applied load–load point displacement curves. The present CZM may be amended to handle other types of fracture or interfacial debonding.